IMPLEMENTATION OF EARLY CHILDHOOD CHARACTER EDUCATION IN THE 2013 CURRICULUM - Susilawati; Wahdini , Erny; Hadi , Sutarto (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The purpose of this study is to describe the 2013 Curriculum in the (1) implementation of character education, (2) values, and (3) education strategy. Early Childhood Education is a form of education fundamental in the life of a child. In the 2013 Curriculum perspective, character education in early childhood integrated in Core Competencies 1 Spiritual Attitudes and Core Competencies 2 Social Attitudes. This study uses a descriptive qualitative approach to design multiple sites with data collected through interviews, observation, and documentation. This research uses a descriptive qualitative approach with a multi-site study design in the PAUD Islamic Integrated Al Khair Barabai and PAUD Negeri Pembina Barabai. Data collection techniques collected through interviews, observation, and documentation. To validate data using triangulation of sources, techniques, and time.  The conclusion of the research is the 2013 curriculum is a source reference in the preparation of programmed activities and habituation activities in addition to the curriculum characteristic of the institutions of each institution. The character values implemented are 18 from the government, Spiritual Attitudes and Social Attitudes. The character education strategy is carried out by the Foundation, the head, educators, educational staff, students, parents who are used through planning, implementation and evaluation.